Rural Market Centres and Development Strategies in Idomaland of Benue State, Nigeria - G. Ogaba, Adadu; A. Omanchi, Samuel; G. A. Abutu, Freeman (Kashere Journal of Humanities, Management and Social Sciences, 2022)
There existed within Benue State several rural market centres. Each of these rural market centres had been pivotal to the economic and social development of their catchment area and the State in spite of their wide limitations which include: low income of traders, poor management and poor and inadequate infrastructure. Besides serving as centres of commerce by providing sustenance, employment, and income for the people and generating revenue for the government, they also serve as centres for exchange of ideas and civilization through social and political interaction. The proper coordination and development of rural market centres will better the lot of the government and the citizenry. It is against this back drop that this paper seeks to examine Rural Market Centres and Rural Development Strategies in Benue State, Nigeria: A focus on Idomaland. The method adopted for the study is basically historical, involving the use of primary sources such as oral interviews, archival materials and secondary source-materials as well as inventory survey (to identify the existing rural market centres and their facilities). It observed that rural market play a very unique role in the process of stimulating change and development in the economy of the state. It therefore recommends among others the provision of special credit scheme that will not demand high collateral or interest from market operators, opening up of market roads for the free flow of goods and services, conduct of market survey to determine among other things shop needs and requirements so as to encourage patronage, the establishment of more market centres in the state and expansion and general development of the State.